Literasi Visual sebagai Pendekatan dalam Pembelajaran Fotografi - Daru Tunggul Aji (Institut Seni Indonesia Yogyakarta, 2021)
Visual Literacy As an Approach To Learning Photography. This article is an overview of the current photographic phenomena. Visual literacy as an approach becomes an offer in the development of photography learning science. As a of discipline, photography has the complexity of learning, just like other scientific disciplines. In photography learning, visual literacy is a significant capital. Visual literacy can be understood as a person's ability to respond to phenomena. It's not just the ability to switch media (design); from the oral to the visual, from the textual to the visual, from the audio to the visiual or from the visual to the other visual forms, and the ability to conduct studies of existing visual works. In photography, it is necessary not only to be processed artistically but also processed that has critical considerations, both from ethics, aesthetics, and perspective, to a phenomenon